A personal perspective of the development and validation of a phase-specific antibody–drug conjugate cytotoxicity potency assay. (May 2013) - Wilson, Robert
Antibody–drug conjugates are anticancer drugs in which a highly potent cytotoxin is linked to an antibody and used in targeted therapy. The cytotoxins are so potent that they themselves have limited therapeutic value, but the antibody provides targeted delivery and, once internalized, the inherent toxicity of the released toxin kills the cancer cells. Targeted delivery is achieved when a unique tumor-associated antigen is expressed on the cancer cell or where the antigen is overexpressed in the cancer relative to normal cells. Targeted therapy minimizes the associated side effects of conventional cancer drug therapy that is directed towards rapidly dividing cells. This paper seeks to discuss salient points in the development and validation of the cell-based potency assay, with particular reference to activities required for phase-specific validation, in the hope these considerations may lead to better data from their application.